A REVIEW OF MODERN MARKETING TOOLS IN THE ERA OF COVID-19 - Ms.Aarushi Rautela, Ms. Priyanka Agrawal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
From past few years digital transformation of retailing activities have become very much important to stay competitive in increasingly dynamic markets. . In recent years, artificial intelligence (AI) has become an emerging trend in various fields: science, business, medicine, automotive and education. AI has also reached marketing. All of the new technologies came up with new implications for marketing activities and have opened up many opportunities for the better performance. Cognitive technology or artificial intelligence (AI) has always a way of capturing the public’s imagination. The emergence of artificial intelligence (AI) has changed the dynamics of the business world. AI holds tremendous potential for vastly altering how marketing is done. Creation of value to customer is very much important for each and every business. Since the last decade many things have been changed like the way people interact with each other. Earlier people were not known about social media but now social media is used heavily by the people of each and every age group. This kind of technology is called Disruptive Innovation. This kind of innovation creates new market trends, value, transportation and communication between people in the society. Modern Marketing helps to improve current marketing tactics and also creates entirely new ways of creating and distributing value to their customers. For example: Social media marketing can allow for a more comprehensive view of customer behavior, predictive analytics of everything , and deeper insights through integration with the help of Artificial Intelligence. New marketing tools like biometrics, voice, and conversational user interfaces offers many ways to add value for brands and consumers alike. These innovations all carry similar characteristics of hyper-personalization, efficient spending, scalable experiences, and deep insights. The technology helps all of the marketers to perform in a better manner, to understand the needs, wants and demand of their customers and enable them to target in a better way and in a customized form. The present research is aimed to review available literature and explore out the modern marketing tools in the era of covid-19.